Pengaruh Profitabilitas, Solvabilitas, Likuiditas, Kompleksitas Operasi Perusahaan dan Ukuran Perusahaan Terhadap Audit Report Lag : Studi Empiris pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024 - Nadya Salwa Nurohmah; Marsellisa Nindito; Hera Khairunnisa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Delays in the submission of audited financial reports (audit report lag) remain a problem for public companies in Indonesia because they can reduce the relevance of information for investors and stalk holders. This study aims to analyze the effect of profitability, solvency, liquidity, operational complexity, and company size on audit report lag in property and real estate companies listed on the Indonesia stock exchange for the period 2022-2024. The research method used is quantitative with panel data regression analysis using Random Effect Model (REM). The results show that profitability and solvency have a negative effect on audit report lag, while company size have no effect. Simultaneously, all independent variables affect audit report lag. This study emphasizes the importance of financial performance and operational complexity in determining the timeliness of audited financial reporting.